MASCULINIZATION OF RAINBOW FISH (MELANOTAENIA BOESEMANI) THROUGH IMMERSION THE LARVAE WITH EXTRACT OF BEE HONEY RESIN AS A NATURAL SUBSTANCE WITH DIFFERENT DOSES - Albasa, Ahmad Rusyda Hafidhi; Hakim, Riza Rahman; Setyono, Budi (xxxx-xxxx)
Abstract. The development of export power ornamental fish offers the potential for ornamental fish the production of Indonesia to global force including the Melanotaenia Boesemani. The difference in value having an economy where a male fish have an economic value higher than the female fish. Based on it, this study aimed to examine the monosex productivity male by the masculinization using natural honey bee resin. Methods used to research this is the method with 4 RAL (0,5 ppm, 1 ppm, 1,5 ppm, and 2 ppm). Data analyzed using analysis (ANOVA) diversity if there is the nature of the treatment and continued with the BNT % 5. The results of the study showed that the bee resin (Propolis) could increase masculinized effect of M.boesemani with average to the percentage male in treatment A 43,92%, B 62,74%, C 50,28%, and D 59,49%, while treatment control of 52,80%. In addition also used the measurement of parameter supporting namely survival rate (SR) with the average treatment A 57,78%, B 44,44%, C 44,44%, D 35,56%, and control of 57,78%. To growth rate (GR) have result treatment A 0,0203g, B 0,0208g, C 0,0215g, D 0,024g, while for control of 0,210g. The quality of water includes the value of doing to the morning ranged from 5,38-8,43 ppm and by day ranged from 5.12-7,67 ppm, while for ph in the morning range 6.5-7.8 and by day ranged from 6.1 a total of 7.3. Based on the research can conclude that Masculinization of M. Boesemani by immersion larvae used honey bee resin (Propolis) with different doses impact against the effects of masculine M.Boesemani best at doses of 1 ppm with percentage 62,74 %.Keyword: M. Boesemani, Masculinization, Propolis extract